Clinical and genetic heterogeneity in Dubowitz syndrome: Implications for diagnosis, management and further research. Issue 4 (22nd December 2018) - Innes, A. Micheil; McInnes, Brenda L.; Dyment, David A.
Abstract : Dubowitz syndrome was described in 1965 as a recognizable syndrome characterized by microcephaly, short stature, eczema, mild developmental delays, and an increased risk of malignancy. Since its original description, there have been over 200 reported cases though no single gene has been identified to explain a significant proportion of affected individuals. Since the last definitive review of Dubowitz syndrome in 1996, there have been 63 individuals with a clinical, or suspected, diagnosis of Dubowitz syndrome reported in 51 publications. These individuals show a markedly wide spectrum with respect to growth, facial gestalt, psychomotor development, and risk of malignancy; genetic causes were identified in 33% (21/63). Seven individuals had deleterious copy number variants, in particular deletions at 14q32 and 17q24 were reported and showed overlap with the Dubowitz phenotype. Several cases were shown to have single gene disorders that included de novo or biallelic pathogenic variants in several genes including NSUN2 and LIG4 frequently identified by next‐generation sequencing methods. It appears that the inability to identify a single gene responsible for Dubowitz syndrome reflects its extreme clinical and genetic heterogeneity. However, detailed phenotyping combined with careful grouping of subsets of unsolved cases and in conjunction with data‐sharing will identify novel disease genes responsible for additional cases. In the interim, for those clinically diagnosed with a Dubowitz phenotype, we recommend assessment by a Medical Geneticist, a microarray and, if available, clinical or research based genome‐wide sequencing. Management suggestions, including decisions regarding malignancy screening in select patients will be discussed.